2015
DOI: 10.5194/acpd-15-11599-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Amazon Tall Tower Observatory (ATTO) in the remote Amazon Basin: overview of first results from ecosystem ecology, meteorology, trace gas, and aerosol measurements

Abstract: Abstract. The Amazon Basin plays key roles in the carbon and water cycles, climate change, atmospheric chemistry, and biodiversity. It already has been changed significantly by human activities, and more pervasive change is expected to occur in the next decades. It is therefore essential to establish long-term measurement sites that provide a baseline record of present-day climatic, biogeochemical, and atmospheric conditions and that will be operated over coming decades to monitor change in the Amazon region a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 190 publications
(214 reference statements)
3
20
0
8
Order By: Relevance
“…This inhomogeneity of land surface properties (and of canopy surface temperatures and surface sensible heat fluxes, ) is related to variations in buoyant production as well as inhomogeneous source distributions for isoprene, both of which have an impact on the variability of the isoprene flux and the mixing ratio (e.g., the variance) and, therefore, on for the isoprenereaction. Comparable to the study by Patton et al (2001), the modelled chemical reactions are for low conditions as found for example in the Amazonian region (e.g., Rohrer et al, 2014) -where one major sink for is isoprene (e.g., Andreae et al, 2015;Karl et al, 2007;Nölscher et al, 2015;Yáňez-Serrano et al, 2015).…”
Section: Guerau Dementioning
confidence: 70%
See 1 more Smart Citation
“…This inhomogeneity of land surface properties (and of canopy surface temperatures and surface sensible heat fluxes, ) is related to variations in buoyant production as well as inhomogeneous source distributions for isoprene, both of which have an impact on the variability of the isoprene flux and the mixing ratio (e.g., the variance) and, therefore, on for the isoprenereaction. Comparable to the study by Patton et al (2001), the modelled chemical reactions are for low conditions as found for example in the Amazonian region (e.g., Rohrer et al, 2014) -where one major sink for is isoprene (e.g., Andreae et al, 2015;Karl et al, 2007;Nölscher et al, 2015;Yáňez-Serrano et al, 2015).…”
Section: Guerau Dementioning
confidence: 70%
“…The ATTO-IOP1 was conducted at the Amazon Tall Tower Observatory (Andreae et al, 2015) (Martinez et al, 2010;Hens et al, 2014 on another cantilever balcony at 40 m along with instruments to measure radiation, isoprene, and water vapour. The balcony faced to the north-east, the direction of the prevailing wind.…”
Section: Atto 2015mentioning
confidence: 99%
“…Further details of CMB can be found in the relative literature (Watson et al, 1984(Watson et al, , 2002USEPA, 2004). The data set of chemical composition in the PM 10 samples during the measurement period and the source profiles reported in our previous works (Bi et al, 2007) were used in the CMB modelling.…”
Section: Vertical Characteristics Of Pm 10 Sourcesmentioning
confidence: 99%
“…A tall tower is commonly used in observation of boundary layer meteorological, micrometeorological and atmospheric chemical variables, e.g. vertical profile and fluxes (Heintzenberg et al, 2008(Heintzenberg et al, , 2013Brown et al, 2013;Andreae et al, 2015). The footprint concept is capable of linking observed data collected at the different height levels of the tower to spatial context.…”
Section: Introductionmentioning
confidence: 99%
“…The Amazon region is the largest rainforest on the planet and it is currently a large focus of scientific research because of its influence on climate. As an example, there are several experiments taking place led by LBA (Large Scale Biosphere-Atmosphere Experiment in Amazonia) together with several countries, where amongst the various objectives is to understand better the interactions between forest and atmosphere Recently, new experiments, such as the ATTO (Amazon Tall Tower Observatory [1]), GoAmazon2014/15 (Green Ocean Amazon [2]) and ACRIDICON [3] have been installed.…”
Section: Introductionmentioning
confidence: 99%